MODULATION AND DAILY BANDING OF MG/CA IN ORBULINA UNIVERSA TESTS BY SYMBIONT PHOTOSYNTHESIS AND RESPIRATION: A COMPLICATION FOR SEAWATER THERMOMETRY? - Eggins S.M.; Sadekov A.; De Deckker P. (My University, 2004)
The Mg/Ca composition of calcium carbonate tests (shells) secreted by planktonic foraminifera is increasingly being employed to estimate past seawater temperatures and reconstruct paleocean and climate records spanning hundreds of thousands of years. We show, using two high-resolution microanalysis techniques, that the final chamber of the planktonic foraminifera Orbulina universa typically comprises between three and six paired, low and high Mg, growth bands. The number and spacing of these bands is consistent with a diurnal origin, modulated by changing pH within the foraminiferal microenvironment due to the day–night, photosynthesis–respiration cycle of algal symbionts. The amplitude of Mg/Ca variation within individual tests and across many daily growth bands cannot be accounted for by seawater temperature in the shallow, euphotic zone habitat of O. universa. Our results indicate the Mg/Ca composition of calcite precipitated by O. universa in nature is strongly influenced by diurnal changes in the biological activity of algal symbionts and the host foraminifer. This brings into question the fundamental premise often made in applying Mg/Ca palaeoseawater thermometry, that the Mg/Ca composition of foraminiferal calcite is determined by seawater temperature, and whether the Mg/Ca composition of other planktonic species that are more widely used for palaeoseawater thermometry are subject to similar influences.